COMBINATION OF MACRAME AND ECO POUNDING WITH COCONUT FIBER DYEING FOR LAMP SHADE - Ardina Putri, Tika Devita; Affanti, Tiwi Bina (Institut Seni Indoensia Surakarta, 2024)
This design is motivated by the use of coconut fiber, which in general the community uses it as fuel and is considered a disturbing waste and causes buildup as coconut production increases. Technological developments and public awareness to return to natural materials will make coconut coir used as a natural dye for fibers (cloth or rope). The use of natural coconut fiber dyes is not widely known even though it has considerable potential to be developed and has a high selling value. The design method used in this design uses the theory of S.P Gustami which consists of 3 stages: namely exploration, design, and embodiment of the work. The exploration stage includes extracting sources of ideas about macrame, eco pounding, lamps and coconut coir. The design stage includes the selection of materials, techniques, and the visual form of the work. The final stage is the embodiment of the work. The final result of this design is in the form of six alternative designs, one of which was chosen to be realized. The realization of the work is in the form of a decorative lampshade on the table which has a function not only as lighting, but also as a decorative element and can beautify a room. This lampshade is presented by applying a combination of macrame and eco pounding techniques which are the novelty of this product. The use of natural coconut coir dyes is one way to preserve the environment.